The body in portuguese advertising - Verissimo, Jorge (2021)
Our research was aimed at understanding the different types of bodies used in Portuguese ads, verifying in which way ads, by transmitting certain images of the human body, convey notions of youth, beauty and seduction, which are normally idealised as having an erotic charge, especially the female body, whose social and effective appeal are essentially of a symbolic nature. So, we studied the different body types; social marks; body expressions and postures; type of scenarios; arguments and appeals in the ads; and the social values inherent to them.